The Impact of the Middle Ear Microbiota on Otitis Media Outcomes: A Meta-Analysis of Longitudinal Studies - Isramilda; Sukma Sahreny (Sriwijaya Journal of Otorhinolaryngology, 2025)
Introduction: Otitis media (OM), a prevalent middle ear inflammation, often involves microbial colonization. The composition of the middle ear microbiota may influence OM outcomes, including recurrence, persistence, and treatment response. This meta-analysis investigated the relationship between the middle ear microbiota and OM outcomes. Methods: Longitudinal studies published from 2018 to 2024 that explored the middle ear microbiota and OM outcomes were systematically searched in PubMed, Embase, and Web of Science. Data on study design, participant characteristics, microbiota analysis, and OM outcomes were extracted. The risk of bias was assessed using the Newcastle-Ottawa Scale. A random-effects model was used to pool effect estimates. Results: A total of 15 studies (n = 2,540 participants) met the inclusion criteria. The middle ear microbiota diversity was significantly lower in children with recurrent OM compared to those without (standardized mean difference [SMD] = -0.45, 95% confidence interval [CI] -0.62 to -0.28, p < 0.001). The presence of specific pathogens, including Streptococcus pneumoniae, Haemophilus influenzae, and Moraxella catarrhalis, was associated with an increased risk of OM recurrence (odds ratio [OR] 1.75, 95% CI 1.32 to 2.31, p < 0.001). Additionally, microbial dysbiosis was associated with delayed resolution of OM and increased antibiotic treatment failure. Conclusion: The middle ear microbiota composition significantly impacts OM outcomes. Reduced diversity and specific pathogens are associated with increased OM recurrence. These findings highlight the potential for microbiota-targeted interventions in OM management.